House decision making system by using soft set theory - Mohd Muhaymin, Ali (2012)
Now-a-days, there are too many characteristics of houses that people like to. Most of the people would find difficulties in find house based on certain circumstances because of too many characteristics that should be complete in continuous living. In addition, not all house would satisfied all side. It is because they have their own expectation for their own houses. The problem is, they do not know how to choose the best choice with the good characteristics for their own houses. By that, this system provides the solution with the objectives, which are to make people easier in making decision and to apply the soft set technique into a real life cases. The parameter for the house such as, the price, the place and many more will be judging by people before they buy it. So, the decision making using soft sets theory would be the solution for the problem. The concept that proposed by Maji et al. is employed to solve the problem of house decision making. By the application of the system, people would be easy to choose the houses according to the satisfactions of characteristics like they want. This report will discuss on the preparation and analysis that been collected throughout the development cycle of this system.